“Concurso municipal de silleteros”, una oportunidad para potenciar el turismo en nuevo colón, Boyacá (2023)
According to the World Tourism Organization (UNWTO), tourism in Colombia has become one of the most discussed topics today, since it has not only contributed to improving the country's economy, but also promotes the optimization of natural resources. historical and cultural promoting sustainable development. For several years, tourism has been undergoing great changes in which not only destinations but also food and festivals become an important part of the tourist experience so that people see different ways of knowing and learning about tourism. That is why this work aims to create a booklet that serves as a means of recognition of the silletas festival of the municipality of Nuevo Colón Boyacá and in the same way the municipality is recognized in the region.